PENGEMBANGAN MANAJEMEN PEMBELAJARAN AGAMA ISLAM - Zaenuri, Zaenuri (Prodi PAI IAILM Suryalaya, 2018)
The success of Islamic Religious Education teachers inimplementing learning is largely determined by their ability toimplement management functions properly. The management of Islamiclearning is a unit of teaching and learning process carried out by theteacher, starting from the planning, the process of activities, to theevaluation and follow-up process that takes place in learning to achievethe objectives of Islamic religious education. The inability of teachers tointernalize management values in the learning process of IslamicReligion can be one of the factors causing the output of students whoare unable to carry out the mission of national education, which is to bea human being who believes and is devoted to Allah SWT. Therefore,improvement of the management of Islamic learning must be carriedout in order to realize an effective learning and achieve the expectedgoals.